A new view for the geodynamics of Ecuador: Implication in seismogenic source definition and seismic hazard assessment. Issue 5 (24th May 2016) - Yepes, Hugo; Audin, Laurence; Alvarado, Alexandra; Beauval, Céline; Aguilar, Jorge; Font, Yvonne; Cotton, Fabrice
Abstract: A new view of Ecuador's complex geodynamics has been developed in the course of modeling seismic source zones for probabilistic seismic hazard analysis. This study focuses on two aspects of the plates' interaction at a continental scale: (a) age‐related differences in rheology between Farallon and Nazca plates—marked by the Grijalva rifted margin and its inland projection—as they subduct underneath central Ecuador, and (b) the rapidly changing convergence obliquity resulting from the convex shape of the South American northwestern continental margin. Both conditions satisfactorily explain several characteristics of the observed seismicity and of the interseismic coupling. Intermediate‐depth seismicity reveals a severe flexure in the Farallon slab as it dips and contorts at depth, originating the El Puyo seismic cluster. The two slabs position and geometry below continental Ecuador also correlate with surface expressions observable in the local and regional geology and tectonics. The interseismic coupling is weak and shallow south of the Grijalva rifted margin and increases northward, with a heterogeneous pattern locally associated to the Carnegie ridge subduction. High convergence obliquity is responsible for the North Andean Block northeastward movement along localized fault systems. The Cosanga and Pallatanga fault segments of the North Andean Block‐South American boundary concentrate most of the seismic moment release in continental Ecuador. Other inner block faults located along the western border of the inter‐Andean Depression also show a high rate of moderate‐size earthquake production. Finally, a total of 19 seismic source zones were modeled in accordance with the proposed geodynamic and neotectonic scheme. Key Points: A reviewed model of Ecuador's geodynamics is used to define seismic source zones Differences in rheology and changes in convergence obliquity explain observed seismicity Shallow and intermediate‐depth seismicity show slab bending and block motion, respectively